2016
DOI: 10.1515/jpem-2014-0477
|View full text |Cite
|
Sign up to set email alerts
|

Cystinosis in Eastern Turkey

Abstract: We detected two distinct mutations, p.T7FX7 (c.18-21del4bp) and p.E227E (c.681 G>A) (homozygous), in the CTNS gene in 11 patients with cystinosis from the East Anatolian region of Turkey. Patients with a homozygous c.681 G>A (p.E227E) mutation are more likely to develop chronic renal failure and should be monitored closely, whereas patients with a p.T7FX7 (c.18-21del4bp) mutation have a milder phenotype. Additionally, metabolic alkalosis does not exclude cystinosis, although cystinosis is a cause of proximal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
2
2
0
Order By: Relevance
“…Moreover, the results of our study showed a slightly increased incidence among the females with a Male: Female ratio of (0.92). Furthermore, the ages of infantile nephropathic cystinosis in our study (ranged 1-12 years, mean= 6.25) were compatible with the studies performed in Turkey [24] (ranged 1.5 -12 years) and the study of Shahkarami et al [25] in Iran (ranged 7 months -11 years). Sequentially, the age of the first presentation in our study was (mean=0.8 year, ranged 0.25-1 year) which was about the same as found in the study of A.Azat [17] in Baghdad (mean = 1.1 years, ranged 0.3-3.5 years).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, the results of our study showed a slightly increased incidence among the females with a Male: Female ratio of (0.92). Furthermore, the ages of infantile nephropathic cystinosis in our study (ranged 1-12 years, mean= 6.25) were compatible with the studies performed in Turkey [24] (ranged 1.5 -12 years) and the study of Shahkarami et al [25] in Iran (ranged 7 months -11 years). Sequentially, the age of the first presentation in our study was (mean=0.8 year, ranged 0.25-1 year) which was about the same as found in the study of A.Azat [17] in Baghdad (mean = 1.1 years, ranged 0.3-3.5 years).…”
Section: Discussionsupporting
confidence: 91%
“…Renal insufficiency is another complication that occurred in 56% of our patients which is near to the results found by A.Azat [17] (41.3%) and Doğan et al [24] (36.3%). Moreover, Hypothyroidism was 20% in our study while its frequency was 3.44% in the study of A.Azat [17].…”
Section: Discussionsupporting
confidence: 82%
“…Cystinosis was found to entail significant morbidity and mortality in our cohort, with many patients experiencing myopathy, ESRD, eye complications, and hypothyroidism. This is in line with previously published literature from the MENA region displaying similar complications in cystinosis patients [18][19][20]. In fact, cystinosis has been previously described as the main cause of renal Fanconi syndrome in childhood, hence entailing electrolyte disturbances, glucosuria, and hypochloremic acidosis [21].…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, the research conducted by Topaloglu et al 4 reported no notable distinction concerning the occurrence of rickets between individuals with these frequently observed mutations and those with other genetic mutations. While typical clinical presentation in cystinosis involves renal tubular acidosis, our study and the others reported cases where patients presented with a hypokalemic, hypochloremic metabolic alkalosis pattern, resembling Bartter syndrome 12,[17][18][19][20] . The exact cause of metabolic alkalosis is not fully understood.…”
Section: Discussionmentioning
confidence: 87%